"We're stuck with what we've got": The impact of lipodystrophy on body image. Issue 9 (27th May 2018) - Adams, Claire; Stears, Anna; Savage, David; Deaton, Christi
Abstract : Aims and objectives: To evaluate the impact of lipodystrophy on body image and how this affects patients' daily lives. Background: Lipodystrophy refers to a group of rare conditions characterised by generalised or partial lack of body fat and is associated with severe metabolic problems, for example, severe insulin resistance, diabetes and pancreatitis. In addition to its metabolic effect, lack of adipose tissue may have a major impact on appearance and cause distressing physical changes. While global research has focused on diagnosis and management, there is no published work investigating the psychological effects of lipodystrophy on body image. Methods: Following ethical approval, participants with lipodystrophy were purposively sampled from the National Severe Insulin Resistance Service in Cambridge, UK, and invited to take part in a semi‐structured interview. Eleven (10 female, one male) interviews were conducted and digitally recorded. Data were analysed using an inductive thematic approach. Results: Four main themes were identified in the data set; "Always feeling appearance was different, " "a better understanding of lipodystrophy is needed, " "feeling accepted" and "there's more to lipodystrophy than managing symptoms." Participants spoke of distressing cosmetic effects related to lack of fat tissue and other changes related to lipodystrophy, contributing to negative body image. For some, negative body image led to feelings of worthlessness impacting daily life and adherence to treatment. Psychological support was lacking but desired by participants. Conclusion: Lipodystrophy contributes to negative body image affecting patients' daily lives. Patients wanted psychological support alongside medical management. Further research is needed to determine how best to deliver psychological support and to evaluate its impact on well‐being and metabolic management. Relevance to clinical practice: The effects of rare diseases such as lipodystrophy on appearance can be distressing for patients. Support beyond medical management is needed to improve patients' daily lives and help them to live well with appearance‐altering conditions.